Separation and purification of cellulase from fermentation broth of sewage sludge - Mukhtaruddin, Muna Tasnim; Alam, Md. Zahangir; Mohd. Salleh, Hamzah; Rashid , Shah Samiur (2010)
In recent years, growing attention has been paid to the conversion of biomass into bioethanol which is considered the cleanest liquid fuel alternative to fossil fuels. One of the major applications of cellulase lies in the process of hydrolysis of cellulosic or lignocellulosic material to produce sugar which can be further fermented to produce ethanol. This study focuses on the purification of cellulases produced from fermentation broth of sewage sludge. In this study, crossflow filteration was used for the purification method using microfiltration (0.45 μm) and utrafiltration (10kD, 5 kD and 1 kD). The results revealed that ultrafiltration with membrane size of 1kD gave the best result for purification of cellulase from fermentation broth of sewage sludge which increases the enzyme activity from 22 U/ml after microfiltration to 50 U/ml after 1 kD of ultrafiltration.